Effect of an electronic medication administration record application on patient safety: A literature review - Triensya, Rafiana (Holistik Jurnal Kesehatan, 2023)
Background: Electronic medication administration records (e-MAR) is a one of information technology utilized by nurses. The transition from paper-based to electronic methods requires consideration of the benefits and risks.Purpose: Identifies the effect of implementing e-MAR on patient safety.Method: Literature study on articles published in 2013-2023, in English, and published in full.Results: 5 articles retrieved from a systematic search on the Proquest and ScienceDirect databases, 1 article was obtained through hand searching, total 6 articles were reviewed in the study.Conclusion: The implementation of electronic medication administration records (e-MAR) has been proven to reduce the risk of medication process errors carried out by nurses thereby increasing patient safety while undergoing treatment at health service facilities.Keywords: Electronic Medication Administration Records; Medication Error; Nurse; Patient Safety.Pendahuluan: Pendokumentasian proses medikasi berbasis elektronik atau (electronic medication administration records (e-MAR) merupakan bentuk pemanfaatan teknologi informasi oleh perawat. Transisi dari metode berbasis kertas ke elektronik perlu dipertimbangkan manfaat dan risikonya.Tujuan: Mengidentifikasi pengaruh implementasi e-MAR terhadap keselamatan pasien.Metode: Menggunakan metode literature review. Penelusuran artikel akademik melalui Online Database diantaranya ProQuest dan ScienceDirect. Dan didapatkan 6 artikel yang sesuai.studi literatur pada artikel yang terpublikasi pada 2013- 2023, berbahasa Inggris, dan terpublikasi lengkap.Hasil: 5 artikel hasil penelusuran sistematis pada database ProQuest dan ScienceDirect , 1 artikel diperoleh melalui hand searching sehingga teridentifikasi 6 artikel yang ditelaah dalam studi ini.Simpulan: Implementasi electronic medication administration record (e-MAR) terbukti dapat menurunkan risiko kesalahan proses medikasi yang dilakukan oleh perawat sehingga meningkatkan keselamatan pasien selama menjalani perawatan di fasilitas pelayanan kesehatan.